An approach to designing sustainable urban infrastructure. (9th January 2019) - Derrible, Sybil
ABSTRACT: Abstract : This article offers a conceptual understanding and easily applicable guidelines for sustainable urban infrastructure design by focusing on the demand for and supply of the services provided by seven urban infrastructure systems. For more than 10, 000 years, cities have evolved continuously, often shaped by the challenges they had to face. Similarly, we can imagine that cities will have to evolve again in the future to address their current challenges. Specifically, urban infrastructure will need to adapt and use less energy and fewer resources while becoming more resilient. In this article, starting with a definition of sustainability, two urban infrastructure sustainability principles (SP) are introduced: (i) controlling the demand and (ii) increasing the supply within reason, which are then applied to seven urban infrastructure systems: water, electricity, district heating and cooling and natural gas, telecommunications, transport, solid waste, and buildings. From these principles, a four-step urban infrastructure design (UID) process is compiled that can be applied to any infrastructure project: (i) controlling the demand to reduce the need for new infrastructure, (ii) integrating a needed service within the current infrastructure, (iii) making new infrastructure multifunctional to provide for other infrastructure systems, and (iv) designing for specific interdependencies and decentralizing infrastructure if possible. Overall, by first recognizing that urban infrastructure systems are inherently integrated and interdependent, this article offers several strategies and guidelines to help design sustainable urban infrastructure systems.